A Novel Approach for Screening Salinity-Tolerant Rice Germplasm by Exploring Redox-Regulated Cytological Fingerprint - Uthpal Krishna Roy; Babita Pal; Soumen Bhattacharjee (Rice Science)
Although metabolic homeostasis disruption, cellular damage, and premature senescence caused by salinity stress are well-documented in the literature, there are few studies investigating cytological changes induced by salinity stress within the altered metabolic landscape of rice, and this study aims to fill that gap. The cytological characterization of root tips (in terms of mitotic index and chromosomal abnormalities such as stickiness, laggards, fragments, bridges, micronuclei, ring chromosomes, and total mitotic abnormalities) was conducted on 10 experimental rice landraces from coastal Bangladesh, grown under post-imbibitional salinity stress (PISS), while correlating these changes with their metabolic status. The results revealed a strong correlation between salinity-induced cytological changes in root cells (mitotic index and chromosomal abnormalities) and the redox interactome status of all experimental rice landraces. The landraces Kutepatnai, Talmugur, Nonakochi, and Benapol, which exhibited a higher ability to mitigate PISS-induced chromosomal abnormalities and improve mitotic index, also showed lower accumulation of oxidative stress markers (protein carbonylation, lipid peroxidation, prooxidant accumulation, oxidative stress index, reactive oxygen species (ROS)-antioxidative stress index, and efficiency of ROS processing via the Halliwell-Asada pathway) compared with more susceptible landraces (Charobalam, Jotaibalam, Kachra, and Lalmota). These findings underscore the role of redox biology in preventing chromotoxic effects under salinity stress. Hierarchical cluster analysis and principal component analysis, used to determine variations and similarities among the experimental rice landraces based on cytological attributes, redox interactome, and physiological phenotypes, classified the landraces according to their salinity tolerance and sensitivity. This study proposes a novel approach for exploring redox-regulated cytological fingerprints as a tool for identifying salinity-tolerant rice landraces.